2018
DOI: 10.1021/acs.langmuir.7b03879
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Interfacial Properties and Processes by Controlling the Rheology and Structure of Poly(N-isopropylacrylamide) Particles at Air/Water Interfaces

Abstract: By combining controlled experiments on single interfaces with measurements on solitary bubbles and liquid foams, we show that poly( N-isopropylacrylamide) (PNIPAM) microgels assembled at air/water interfaces exhibit a solid to liquid transition changing the temperature, and that this is associated with the change in the interfacial microstructure of the PNIPAM particles around their volume phase transition temperature. We show that the solid behaves as a soft 2D colloidal glass, and that the existence of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 50 publications
5
60
0
Order By: Relevance
“…One model attributes the destabilization of the emulsion to the collapse of the interfacially adsorbed microgels into smaller spheres which cover less area and thus are less efficient stabilizers. [51][52][53] Additionally, it was proposed that microgels may desorb from the oil/water interface to the oil phase due to their increased hydrophobicity, 53,54 which, however, does not seem to occur in all reported experimental scenarios. 55,56 It was also suggested that microgels form aggregates and multilayers at the oil/water interface, 44,45,56 which has been experimentally visualized for the inverse case of water in oil emulsions.…”
Section: Hysteresis Of the Volume Phase Transitionmentioning
confidence: 97%
See 3 more Smart Citations
“…One model attributes the destabilization of the emulsion to the collapse of the interfacially adsorbed microgels into smaller spheres which cover less area and thus are less efficient stabilizers. [51][52][53] Additionally, it was proposed that microgels may desorb from the oil/water interface to the oil phase due to their increased hydrophobicity, 53,54 which, however, does not seem to occur in all reported experimental scenarios. 55,56 It was also suggested that microgels form aggregates and multilayers at the oil/water interface, 44,45,56 which has been experimentally visualized for the inverse case of water in oil emulsions.…”
Section: Hysteresis Of the Volume Phase Transitionmentioning
confidence: 97%
“…PNiPAm microgels are known to stabilize oil/water emulsions, which are stable below the VPTT and can be destabilized by heating above the VPTT. 42,43,[52][53][54][55][56][44][45][46][47][48][49][50][51] Various explanations regarding this stimuli-responsive behavior were proposed. One model attributes the destabilization of the emulsion to the collapse of the interfacially adsorbed microgels into smaller spheres which cover less area and thus are less efficient stabilizers.…”
Section: Hysteresis Of the Volume Phase Transitionmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous works to obtain smart microgels using surfactant free method are based on N-isopropyl acrylamide (NIPAm) polymers and its copolymers with acrylic (AA), methacrylic (MA), or 2-acrylamido-2-methyl propane sulfonic acids (AMPS) [28][29][30]. In this category of microgels, the low temperature and high pH conditions increased the swelling of particles and formed more stable Mickering emulsions.…”
Section: Introductionmentioning
confidence: 99%